Barriers To Successful Implementation of STEM Education - James A. Ejiwale (Journal of Education and Learning (EduLearn), 2013)
The implementation of STEM education in schools across the globe is to prepare the future workforce with strong scientific and mathematical backgrounds to enhance skills development across STEM disciplines. However, for STEM education to achieve its goals and objectives, addressing the barriers to STEM education should start by fixing the problems at the elementary, junior and senior high school levels; the grassroots and potential feeders to colleges and universities. Since many nations including the United States of America is in dire need of the workforce with adequate preparation in science and mathematics to help address the nation’s economy that is in shambles, the barriers to its successful implementation should be identified and addressed. In this paper, (a) the definition of STEM education and (b) some barriers to successful implementation of STEM education are discussed and elaborated.